Health Status Determinants Lifestyle, Environment, Health Care Resources and Efficiency - Joumard, Isabelle (OECD Economics Department Working Papers, 2008)
This paper aims to shed light on the contribution of health care and other determinants to the health status of the population and to provide evidence on whether or not health care resources are producing similar value for money across OECD countries. First, it discusses the pros and cons of various indicators of the health status, concluding that mortality and longevity indicators have some drawbacks but remain the best available proxies. Second, it suggests that changes in health care spending, lifestyle factors (smoking and alcohol consumption as well as diet), education, pollution and income have been important factors behind improvements in health status. Third, it derives estimates of countries' relative performance in transforming health care resources into longevity from two different methods - panel data regressions and data envelopment analysis - which give remarkably consistent results. The empirical estimates suggest that potential efficiency gains might be large enough to raise life expectancy at birth by almost three years on average for OECD countries, while a 10% increase in total health spending would increase life expectancy by three to four months